Formulating Islamic Da‘wah Strategies for Generation Z in Indonesia: a SWOT Analysis - Azwar, Azwar; Usman, Abur Hamdi; Ravi Abdullah, Mohd Farid (Al-madinah: Journal of Islamic Civilization, 2025)
This study aims to identify the strengths, weaknesses, opportunities, and threats (SWOT) of Islamic da‘wah targeting Generation Z (Gen-Z) in Indonesia, focusing on the formulation of innovative and adaptive strategies. Employing a qualitative descriptive-analytical method, the research draws on participatory observation and document analysis. The findings show that Islamic da‘wah has significant strengths in adapting to digital platforms such as social media and video-sharing apps, with visually engaging content that resonates with Gen-Z. Community-based approaches also foster emotional engagement with Islamic values. However, weaknesses remain, including limited digital literacy among preachers and the lack of structured, consistent content. Conventional da‘wah models are often too formal, making them less appealing to Gen-Z’s preference for interactive and expressive communication. Opportunities lie in the expansive reach of digital media and Gen-Z’s growing interest in social and global issues. Da‘wah that promotes values like justice, compassion, and social responsibility aligns with Gen-Z’s concerns. Nevertheless, several threats challenge the effectiveness of da‘wah, including the unregulated flow of online information, exposure to misleading or radical content, and the influence of pop culture and hedonism, which can fuel skepticism toward religious symbols. Social polarization further necessitates inclusive and non-dogmatic approaches. The study concludes that effective da‘wah strategies should strengthen digital competencies among da'i, develop structured content, and align messaging with Gen-Z’s digital culture while emphasizing Islam’s universal values. A strategic, contextual approach is essential for ensuring that Islamic da‘wah remains relevant, engaging, and impactful for Gen-Z.